2009
DOI: 10.1289/ehp.11769
|View full text |Cite
|
Sign up to set email alerts
|

Association between Frequency of Chromosomal Aberrations and Cancer Risk Is Not Influenced by Genetic Polymorphisms in GSTM1 and GSTT1

Abstract: BackgroundThe frequency of chromosomal aberrations (CA) in peripheral blood lymphocytes of healthy individuals has been associated with cancer risk. It is presently unclear whether this association is influenced by individual susceptibility factors such as genetic polymorphisms of xenobiotic-metabolizing enzymes.ObjectivesTo evaluate the role of polymorphisms in glutathione S-transferase (GST) M1 (GSTM1) and theta 1 (GSTT1) as effect modifiers of the association between CA and cancer risk.MethodsA case–control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 39 publications
2
17
1
Order By: Relevance
“…In the present study we found a significant influence of GSTM1 on the effect of exposure to genotoxic agents. This polymorphic gene has been extensively studied, as individuals presenting the null genotype have a decreased ability to detoxify carcinogens, thus having a higher sensitivity to genetic damage and an increased cancer risk (Rossi et al, 2009). Accordingly, our results showed among the control group a higher CA-chromosome MR in the GSTM1 null individuals.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In the present study we found a significant influence of GSTM1 on the effect of exposure to genotoxic agents. This polymorphic gene has been extensively studied, as individuals presenting the null genotype have a decreased ability to detoxify carcinogens, thus having a higher sensitivity to genetic damage and an increased cancer risk (Rossi et al, 2009). Accordingly, our results showed among the control group a higher CA-chromosome MR in the GSTM1 null individuals.…”
Section: Discussionsupporting
confidence: 57%
“…lower CA-total and CA-chromosome MRs . Two of the major studies which evaluated the influence of GSTM1 deletion on CA frequencies were performed by Rossi et al (2009) andSkjelbred et al (2011). None of these studies, that investigated cancer cases vs. control individuals and a population of healthy individuals, respectively, found any significant effect of these modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Human cancers are often associated with chromosomal instability (both numerical and structural CAs) in the cells (11)(12)(13); these aberrations are also considered as causative events in malignant transformation (14). Frequencies of CA in PBL are predictive for cancer risk in prospective epidemiological studies (15)(16)(17), and patients with many types of cancer show elevated CAs at the time of diagnosis (10,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, chromosomal aberration analysis, micronucleus, and comet assay have emerged as most reliable in evaluation of genotoxic effect of human exposure to pesticides. Among them, chromosomal aberrations and micronuclei as biomarkers of the effect were also proved to be good predictors in cancer risk assessment (Fenech, 2007;Rossi et al, 2009). …”
Section: Genetic Toxicologymentioning
confidence: 99%